Natural Rigid and Hard Plastic Fabricated from Elastomeric Degradation of Natural Rubber Composite with Ultra-High Magnesium Carbonate Content - Dasaesamoh A. (2023)
It is known that natural rubber is an elastomeric polymer; hence, the main uses are usually limited to soft applications. For the process to reverse the elastomeric effect of natural rubber to obtain rigid plastic from a natural material, an ultra-high amount of magnesium carbonate particles was added to the natural rubber to study the effect of magnesium carbonate in the reduction of elastomeric properties. High magnesium carbonate ratios of 80–180 phr were mixed in the natural rubber in the latex form to maximize the mixing capability since it was more difficult to achieve these mixture ratios with only two roll mill or extruder processes. The more magnesium carbonate powders in the composite, the higher torques were measured from the moving die rheometer (MDR) test. The powder was thoroughly mixed inside the composite, which was observed from energy-dispersive X-ray spectrometer (EDX) mapping; however, the matrix of composites was filled with porosity due to the CO2 formation when latex with magnesium carbonate was assimilated with acid during the vulcanization process. The strength of the composite dropped, and the elongations were shortened. On the other hand, the hardness of composites was drastically increased. The composite lost the elastomeric property, and the hard natural rubber composites were obtained.